Influence of Material Properties on the Ballistic Performance of Ceramics for Personal Body Armour - Christian Kaufmann; Duane Cronin; Michael Worswick; Gilles Pageau; Andre Beth (Shock and Vibration)
In support of improved personal armour development, depth of penetration tests have been conducted on four different ceramic materials including alumina, modified alumina, silicon carbide and boron carbide. These experiments consisted of impacting ceramic tiles bonded to aluminum cylinders with 0.50 caliber armour piercing projectiles. The results are presented in terms of ballistic efficiency, and the validity of using ballistic efficiency as a measure of ceramic performance was examined. In addition, the correlation between ballistic performance and ceramic material properties, such as elastic modulus, hardness, spall strength and Hugoniot Elastic Limit, has been considered.